SERTIFIKASI DOSEN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PADA INSTITUT AGAMA ISLAM (IAI) NUSANTARA BATANGHARI - Yusup, Muhammad; -, Marzani (UIN Imam Bonjol Padang, 2019)
Achievement of the purpose of implementing Higher Education is carried out by lecturers as the core implementing academic process. To support the goal process, the government is making various efforts to prosper educators. One of the government policies in the education sector is certification for educators. The state of certified lecturers at IAI Nusantara Batanghari began to increase in terms of performance compared to before being certified. The rationale and foundation of the implementation of certification activities for these lecturers have been regulated in accordance with the laws, regulations and decisions related to certification. As a lecturer who plays a very important role, ideally he has competencies that can be relied upon as educational staff; these competencies at least consist of personal competencies, professional competencies and social competencies. This research is a field research with a qualitative approach namely; research whose procedures produce descriptive data in the form of written or oral words from people and observed behavior. The quality of lecturer learning at IAI Nusantara Batanghari is based on four competencies, namely pedagogical competence, professional competence, social competence and personality competence.